Ultrasound-assisted near nerve method in nerve conduction study for the diagnosis of tarsal tunnel syndrome. A case report - Nakano, Haruki (Clin Neurophysiol Pract, 2020)
OBJECTIVES: The sensitivity of nerve conduction studies (NCSs) of the medial and lateral plantar nerves for the diagnosis of tarsal tunnel syndrome (TTS) is not high enough. The near nerve method (NNM) is a recording technique for NCSs that allows the recording of large, clear potentials. The NNM was reported to improve the sensitivity of diagnoses of TTS. However, the NNM requires special skill using electrical motor threshold in positioning a needle electrode correctly. Thus, we performed the NNM with the aid of ultrasound imaging (ultrasound-assisted). The aim of this case report is to show the utility of ultrasound-assisted NNM in the electrodiagnosis of TTS. CASE REPORT: A 69-year-old woman presented with paresthesia on the lateral sole of her right foot. Ultrasound imaging showed a space occupying lesion (SOL) posterior to the medial malleolus, caused by tenosynovitis, as discovered after surgery. We performed an NCS of the medial and lateral plantar nerves with ultrasound-assisted NNM. Ultrasound-assisted NNM allowed us to easily determine the needle insertion site just proximal to the SOL and to avoid penetrating the SOL and the vessels, and, furthermore, simplified moving the needle electrode toward the target nerve. The results of the NCS revealed that there was severe injury to the lateral plantar nerve and no injury to the medial plantar nerve. CONCLUSIONS: In the NCS of the medial and lateral plantar nerves with NNM to diagnose TTS, ultrasound-assisted NNM can be useful for simplicity and safety.